2D Intrinsic Ferromagnetic MnP Single Crystals. Issue 29 (11th June 2020) - Sun, Xian; Zhao, Shasha; Bachmatiuk, Alicja; Rümmeli, Mark H.; Gorantla, Sandeep; Zeng, Mengqi; Fu, Lei
Abstract: 2D intrinsic ferromagnetic materials are highly anticipated in spintronic devices due to their coveted 2D limited magnetism. However, 2D non‐layered intrinsic ferromagnets have received sporadic attention, which is largely attributed to the fact that their synthesis is still a great challenge. Significantly, manganese phosphide (MnP) is a promising non‐layered intrinsic ferromagnet with excellent properties. Herein, high‐quality 2D MnP single crystals formed over liquid metal tin (Sn) is demonstrated through a facile chemical vapor deposition technique. The introduction of liquid metal Sn provides a fertile ground for the growth of 2D MnP single crystals. Interestingly, 2D MnP single crystals maintain their intrinsic ferromagnetism and exhibit a Curie temperature above room temperature. The research enriches the diversity of 2D intrinsic ferromagnetic materials, opening up opportunities for further exploration of their unique properties and rich applications. Abstract : 2D manganese phosphide (MnP) single crystals with high‐quality are successfully synthesized on liquid metal. Notably, magnetic studies demonstrate that 2D MnP single crystals persist in the intrinsic ferromagnetism above room temperature. The research creates a fascinating platform for exploring their unique properties and rich applications on the 2D level.